Synthesis of Mg-Ferrite nanoparticles via auto combustion method and investigation their structural, morphological and magnetic properties - Ibrahim F. Waheed; Faiz M. AL-Abady; Baidaa M. Ali (Tikrit Journal of Pure Science, 2019)
Magnesium ferrite (MgFe2O4) nanoparticles is prepared by sol-gel auto combustion method and calcinated at (200,450, 900) °C. The capping agent was urea and (Mg(NO3)2.6H2O) and (Fe(NO3)3.9H2O) nitrates as sources of metal. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) characteristic show clear modes of the cubic Mg-ferrite structure formation. Infrared spectrum of metal-oxygen vibration at (703-636) and (574-433) cm−1 show the tetrahedral and octahedral site of Mg-ferrite structure. Scanning Electron Microscope (SEM) images shown pure crystalline microstructure with polyhedral shapes and very small numbers of globular small particles. The crystallite size of Mg-ferrite is calculated using Debye-Scherrer relation and was in the range of 29 nm.